The NK1 receptor antagonist serlopitant for treatment of chronic pruritus. (3rd August 2019) - Ständer, Sonja; Spellman, Mary C.; Kwon, Paul; Yosipovitch, Gil
ABSTRACT: Introduction : Pruritus is a common symptom associated with several potential underlying causes, including both dermatologic and systemic diseases; it can also occur without an identifiable cause. Current treatment options are limited and most patients experience impaired quality of life. Serlopitant is a neurokinin 1 (NK1 ) receptor antagonist under development for the treatment of pruritus associated with various dermatologic conditions and chronic pruritus of unknown origin. Areas covered : This review describes the epidemiology and unmet needs of patients with chronic pruritus, focusing specifically on patients with prurigo nodularis, psoriatic itch, and chronic pruritus of unknown origin; the rationale for targeting the NK1 receptor for treatment of chronic pruritus; and the clinical development of serlopitant, including efficacy and safety data from completed phase II studies. Expert opinion : There is an unmet need for novel, safe, and effective therapies to treat chronic pruritus. Serlopitant has shown promising efficacy, safety, and tolerability across different patient populations, including adolescents and elderly patients. In contrast to less convenient administration options, serlopitant is a once-daily oral tablet, which is expected to facilitate compliance. Trial registration: ClinicalTrials.gov identifier: NCT00290563. Trial registration: ClinicalTrials.gov identifier: NCT00835718. Trial registration: ClinicalTrials.gov identifier: NCT03282591. Trial registration: ClinicalTrials.gov identifier: NCT01951274. Trial registration: ClinicalTrials.gov identifier: NCT02196324. Trial registration: ClinicalTrials.gov identifier: NCT02975206. Trial registration: ClinicalTrials.gov identifier: NCT03343639. Trial registration: ClinicalTrials.gov identifier: NCT03546816. Trial registration: ClinicalTrials.gov identifier: NCT03677401. Trial registration: ClinicalTrials.gov identifier: NCT03540160. Trial registration: ClinicalTrials.gov identifier: NCT03841331.